TATTOO GANESA, TATU BAGI UMAT HINDU - I Gusti Ketut Widana (Pascasarjana Universitas Hindu Indonesia, 2018)
The influence of tourism for the majority of Balinese Hindus making the existence of Bali Island a enter of national tourism development, even international. Added to the acceleration of the rate of modernization with the wave of globalization that is so powerful, whether or not it has entered and touched, even slowly but surely has eroded the established order of Bali’s scene with all its changes. At least in terms of openness, Balinese people (Hindus) tend to be so easy to accept outside elements (foreign), almost without selection. The permissiveness or the letting go of what comes has made the Hindus so vulnerable to be affected, especially by the negative, destructive and counterproductive influences to the religiously defended values that are morally vested in the value of money. Like the commodification of the values of holiness or sacredness of the sacred symbol of Hindu like god Ganesha which by the tourism businessmen has made as Tattoo object with the human body media (male/ female) as a canvas, which is not uncommonly painted on the sensual organ. The Tattooo of Dewa Ganesha on the human body is actually a Tatu (wound) that slashed even sliced the heart, feelings and inner state of thhe Hindus, because the figure of Ganesha worshiped has been dumped, harassed and even tainted by sacredness solely for the taste of tourists for the benefit of material gain/ financial for the perpetrators of tourism.